Analisis Kestabilan Lereng BT 02 Jalan Masuk Tambang Bawah Tanah PT. Nusa Alam Lestari di Desa Salak, Kecamatan Talawi Kota Sawahlunto, Provinsi Sumatra Barat - Rizka Anazakia; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2021)
PT. Nusa Alam Lestari is a company which engaged in coal mining business in Sawahlunto City.The level of mine slope stability is the most important factor that must be considered in the sustainability of mining activities. The writer conducted a research at the mining slope location of PT. NAL, which is at the coordinates of S00˚43'27,0 "/ E100˚47'11,1" with slope height 38m and slope 81˚.In this study, the writer used kinematic analysis with dips software and slope stability analysis using the Finite Element method. Based on the data from the kinematic analysis, the percentage value of potential landslides that occur at the research location is the plane failure which has a landslide potential of 25.37%. Second, the results of the analysis of the safety factor (SF) of the slope using the Finite Element method show that the results of the single slope analysis of the actual value obtained are SF = 1.22 (natural conditions) and SF = 0.88 (saturated conditions). Third, to obtain a safe SF, namely 1.25, a change in the geometry of the slope was carried out by reducing the slope angle from 81 ° to 72 ° in saturated conditions so that the SF value 1.25.Keywords: Open Mining, Slope Geometry, Finite Element Method, Safety Factor